“Academic-practitioner” as governance outcomes: a critical analysis of identity reinvention in Thai higher education reform 4.0 during the MHESI era - Sukhampha, Rangsan (Frontiers in Education, 2025)
IntroductionThe article examines the rise of “academic-practitioners” concerning the reform of Thai higher education 4.0 following the putting into force of the 20-year long-term higher education plan 2018–2037, which has led to significant structural changes in higher education. This reform is situated within the global context of the Fourth Industrial Revolution (4IR) and the competing demands of Education 4.0 and the emerging human-centric goals of Education 5.0.MethodsThe analysis employs a two-layered approach, combining critical policy analysis with the author’s autoethnographic account of institutional implementation, grounding the claims in both top-down discourse and bottom-up experience.Findings/discussionThe article reveals that the construction of academic-practitioner identity serves as the means and the ends, including as a key governance tool to re-orient higher education towards national economic priorities. Specifically, given the alterations occurring at the university level and the unique circumstances within individual universities, professors must alter the approaches in which they work. As a consequence, university lecturers have seemingly transitioned from being academics to becoming practitioners or mixed, the so-called “academic-practitioners.” This is a compelling matter in an overview examination of the higher education reform process that impacts the standing and positionality of university professors, resulting in a transformation of lecturers’ status. The identities of academics and practitioners are influenced by the creation of systems and mechanisms at the national and ministerial levels. Academic practitioners, in the case of Thailand, emerged from several factors, such as the middle-income trap, decreasing the birth rate, and the aging population, to which the government responded with the 4.0 strategic approach. As a result, universities are anticipated to co-produce innovation in accordance with this strategy. Nonetheless, there is criticism that an overemphasis on innovation may result in the oversight of other critical elements. Practically, the villagers participate in entrepreneurial endeavors, fostering sustainable development in collaboration with universities. An approach for improving the performance of Thai universities that is directed by quality assessments and tools to guarantee that operations align with global, regional, and national educational standards. Nonetheless, it remains a long journey towards sustainability and has faced considerable criticism.ConclusionAn analysis of the Thai higher education reform during the MHESI Era can deepen the understanding of global-national social governance in educational policies in countries that are faced with changing systems and governance.